Transgenic tobacco plants expressing antisense ferredoxin-NADP(H) reductase transcripts display increased susceptibility to photo-oxidative damage - Sonnewald, Uwe; et al. (Plant Journal, 2003)
Ferredoxin-NADP(H) reductase (FNR) catalyses the final step of the photosynthetic electron transport in chloroplasts. Using an antisense RNA strategy to reduce expression of this flavoenzyme in transgenic tobacco plants, it has been demonstrated that FNR mediates a rate-limiting step of photosynthesis under both limiting and saturating light conditions. Here, we show that these FNR-deficient plants are abnormally prone to photo-oxidative injury. When grown under autotrophic conditions for 3 weeks, specimens with 20-40% extant reductase undergo leaf bleaching, lipid peroxidation and membrane damage. The magnitude of the effect was proportional to the light intensity and to the extent of FNR depletion, and was accompanied by morphological changes involving accumulation of aberrant plastids with defective thylakoid stacking. Damage was initially confined to chloroplast membranes, whereas Rubisco and other stromal proteins began to decline only after several weeks of autotrophic growth, paralleled by partial recovery of NADPH levels. Exposure of the transgenic plants to moderately high irradiation resulted in rapid loss of photosynthetic capacity and accumulation of singlet oxygen in leaves. The collected results suggest that the extensive photo-oxidative damage sustained by plants impaired in FNR expression was caused by singlet oxygen building up to toxic levels in these tissues, as a direct consequence of the over-reduction of the electron transport chain in FNR-deficient chloroplasts.
Keywords: ferredoxin-NADP(H) reductase; antisense; transgenic tobacco plants; oxidative stress; photoinhibition